Baby Massage Education for Baby Growth and Development at Clinic Sahabat Bunda - Turnip, Meria; Br Panjaitan, Delita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Baby growth and development is an indicator of baby health. Data from WHO shows that a number of toddlers experience motor disorders, which can include fine motor skills and gross motor skills. Infancy is considered a critical and environmentally sensitive period, so optimizing care during this period has a significant impact on the child's well-being. Baby massage is recognized as a useful therapy for encouraging children's growth and development. However, mothers' low knowledge of independent baby massage techniques can affect their skills in carrying out baby massage. Therefore, an educational approach through counseling is considered an effective strategy for increasing mothers' understanding and skills. Community service activities (PKM) carried out at the Sahabat Bunda Midwife Clinic involve material presentations, question and answer discussions, and demonstrations as learning methods. The results of the PKM show that the material presented can be well understood and responded to by mothers. Positive feedback received indicates achievement of extension targets. Significantly, mothers' knowledge and skills regarding baby massage increased, as seen from their ability to answer questions and carry out baby massage demonstrations. It is hoped that through this PKM activity, mothers can be independent in carrying out baby massage, so that they can make a positive contribution to the optimal growth and development of their babies.